HEXAGON FRAUD IN FRAUDULENT FINANCIAL STATEMENTS: THE MODERATING ROLE OF AUDIT COMMITTEE - Nugroho, Dwiyanjana Santyo; Diyanty, Vera (UI Scholars Hub, 2022)
This paper aims to examine the effect of the fraud hexagon on fraudulent financial statements (FFS), and the audit committee (AC)'s role in moderating this relation. The research model uses logit regression with data on all non-financial companies in Indonesia ranging from 2016 to 2020, which were obtained from annual reports and Thomson Reuters. The sensitivity test uses a coefficient difference test based on the Overall Manipulation Index. This study shows that the probability of FFS is higher when the manager has the stimulus, opportunity, and capability. On the other hand, rationalization and collusion do not affect the probability of FFS. Interestingly, managers with high ego do not commit fraudulent financial reporting. The AC can minimize the stimulus, opportunity, and capability of the manager to make FFS. On the other hand, the AC cannot minimize the rationalization, ego, and collusion network of the manager. Theoretically, this study contributes to developing the situational action theory literature related to FFS and the fraud hexagon framework. This study provides academic implications that the arguments and empirical research findings that examine the behavior of managers in committing fraudulent financial reporting can be built not only based on the proxies used, but also by referring to the fraud theoretical framework.